Gender Differences in the Pathogenesis and Management of Heart Disease (Springer International Publishing, 2018)
This book reviews all aspects of the diagnosis and management of heart disease in women, covering areas such as gender differences in metabolic syndrome, hypertension and atherogenesis. Gender differences in cardiovascular diseases are widespread, but while gender medicine takes into account the effects of sex and gender on the health of women and men, traditionally, women have been underrepresented in cardiovascular clinical trials, in management of different cardiac diseases and drug use. Gender Differences in the Pathogenesis and Management of Heart Disease deals with the gender-specific differences in cardiac physiology and diseases and brings into perspective the critical significance of gender in management of cardiovascular disease presentations and management. As such it is of enormous use to all clinical staff who manage women with cardiovascular disease.